Physiological Ischemic Training Promotes Brain Collateral Formation and Improves Functions in Patients with Acute Cerebral Infarction - Zhen, Xiaoyue; Zheng, Yu; Hong, Xunning; Chen, Yan; Gu, Ping; Tang, Jinrong; Cheng, Hong; Yuan, Ti-Fei; Lu, Xiao (Frontiers in Neurology, 2016)
Objectives To observe the effectiveness and mechanisms of physiological ischemic training (PIT) on brain cerebral collateral formation and functional recovery in patients with acute cerebral infarction. Methods Twenty eligible patients with acute cerebral infarction were randomly assigned to either PIT group (n=10) or control group (n=10). Both groups received 4 weeks of routine rehabilitation therapy, while an additional session of PIT which was consisted of 10 times of maximal voluntary isometric handgrip for 1 minute followed by 1 minute rest was prescribed for patients in the PIT groups. Each patient was trained with 2 sections a day and 5 days a week for 4 weeks. The Fugl-Meyer assessment (FMA), the Modified Barthel Index (MBI) and SF-36 were applied for the evaluation of motor impairment, activity of daily living and quality of life at the baseline and endpoint. MRI was applied to detect the collateral formation in the brain. The concentration of VEGF and EPCs number in plasma were also tested at the endpoint. Results Demographic data were consistent between experimental groups. At the endpoint, the scores of the FMA, MBI and SF-36 were significantly higher than that at baseline. As compared to the control group, the score of FMA and SF-36 in PIT group was significantly higher, while no significant difference was detected between groups in terms of MBI. Both groups had significantly higher collateral blood flow (CBF) level at endpoint as compared to that at baseline. Moreover, the CBF level was even higher in the PIT group as compared to that in the control group after 4 weeks training. The same situations were also found in the plasma VEGF and EPCs assessment. In addition, positive correlations were found between FMA score and CBF level (r=0.686, P<0.01), CBF level and VEGF concentration (r=0.675, P<0.01), and VEGF concentration and EPC number (r=0.722, P<0.01). Conclusions PIT may play an important role in increasing the expression of VEGF and recruitment of EPCs and in turn facilitate the angiogenesis which may help to improve the function of the patients with stroke.